2018
DOI: 10.4236/ojn.2018.87032
|View full text |Cite
|
Sign up to set email alerts
|

A Spider in a Broken Web: Nurses’ Views on Discharge Planning for Older Patients after Hip Fracture Surgery Who Live in their Own Homes in Rural Areas

Abstract: Introduction: The in-hospital rehabilitation of patients who have undergone surgery for hip fracture requires a team-based effort, in which nurses play an all-embracing role throughout the patients' hospital stays. Although discharge planning has been widely studied, little is known about discharge planning from hospitals to homes in rural settings. Aim: To describe nurses' views on discharge planning for older patients after hip fracture surgery who live in their own homes in rural areas. Methods: A qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Previous work discussed the idea that patients required greater support during pre-discharge (Segevall et al , 2018). However, this work provides no information as to the actual meaning of support or details about the process to share this or augment the patients' voices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work discussed the idea that patients required greater support during pre-discharge (Segevall et al , 2018). However, this work provides no information as to the actual meaning of support or details about the process to share this or augment the patients' voices.…”
Section: Discussionmentioning
confidence: 99%
“…Internationally, the situation is no different. A recent Swedish study found that nurses believe patients require better support from healthcare services to prepare for home (Segevall et al , 2018). This study suggested that patients were not adequately heard or supported during the inpatient stay and that the discharge process requires shared decision making to generate understanding between staff and patients about post-discharge requirements.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The event also impacts their close relatives, that is, people who are close to them emotionally [ 2 ]. Close relatives are highly valued during recovery after hip fracture surgery by both older people and healthcare personnel, as they provide help and support in the hospital and after discharge [ 1 , 3 , 4 , 5 ]. While close relatives want to be a part of the older person’s life and provide practical and emotional support during recovery [ 2 ], the time to prepare and develop skills that might be useful is short, due to the unexpected nature of the fracture and the short length of such hospital stays [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other patients think that they are not competent enough and, thus, trust the medically trained healthcare professionals to make decisions in their best interest (Alharbi et al, 2014 ; Larsson et al, 2011 ). In addition, some patients lack information to make decisions and end up agreeing to suggestions from the healthcare professionals (Segevall et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research about patients’ experience of participation in care during a hospital stay has shown that patients do not always feel involved in care nor are they given the opportunity to make their own decisions (Bagnasco et al, 2019 ; Dyrstad et al, 2015 ; Malmgren et al, 2014 ). Information has been suggested to be a key aspect; to be involved in decision making, one has to be sufficiently informed about, for instance, the procedures they are going to undergo as well as their care plan (Bagnasco et al, 2019 ; Segevall et al, 2018 ). Å. Nilsson et al ( 2018 ) found that being prepared for the hospital stay is critical for experiencing participation in care.…”
Section: Introductionmentioning
confidence: 99%